Oil spill related heavy metal: a review = Logam berat berkaitan tumpahan minyak: satu ulasan - Mustafa, Ahmad Dasuki; Juahir, Hafizan; Yunus, Kamaruzzaman; Amran, Mohammad Azizi; Che Hasnam, Che Noraini; Azaman, Fazureen; Zainal Abidin, Ismail; Azmee, Syahril Hirman; Sulaiman, Nur Hishaam (Universiti Kebangsaan Malaysia (UKM), 2015)
Oil spill occurs every day worldwide and oil contamination is a significant contributor for the higher levels of heavy metals in the environment. This study is purposely to summarize the heavy metals which significant to major oil spill incidents around the world and effects of toxic metals to human health. The study performed a comprehensive review of relevant scientific journal articles and government documents concerning heavy metals contamination and oil spills. Overall, the heavy metals most frequently been detected in oil spill related study where Pb>Ni>V>Zn>Cd and caused many effects to human health especially cancer. In conclusion, the comparison of heavy metal level between the post - spill and baseline levels must be done, and implementation of continuous monitoring of heavy metal. In addition, the result based on the strategies must be transparent to public in order to maintaining human health.